KEJAHATAN DAN CAMPUR TANGAN TUHAN (Sebuah Tinjauan Teodesi dan Teologi Islam) - syafieh, syafieh (Program Pascasarjana IAIN Langsa, 2019)
This article discusses God 's omniscience and interference in the theological and Islamic's theological perspectives. Theodical problem that centered on causality and the administration of God since the days of Greece God presented as a defendant. Berger uses theodicy concept to give meaning to the suffering experienced by humans in the world, while simultaneously promising happiness